2015
DOI: 10.4103/2347-8659.167301
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural brain abnormalities, affective temperaments, and suicidal behavior in patients with major depression

Abstract: According to magnetic resonance imaging (MRI) studies, brain white matter (WM) abnormalities have been suggested to play a critical role in the pathogenesis of major depressive disorder (MDD) and related suicidal behavior. However, MRI findings may be limited by low spatial resolution; therefore, an important contribution to the understanding of the role and significance of WM alterations derived by the development of the most recent magnetic resonance techniques, such as diffusion tensor imaging (DTI). Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 119 publications
(168 reference statements)
1
4
0
Order By: Relevance
“…In this study, we found generally decreased MD and increased FA in the MDD subjects compared to the healthy controls. While many studies have reported increased MD and decreased FA in MDD compared to HC (Arnold et al, 2012; Benedetti et al, 2011; Osoba et al, 2013; Serafini et al, 2015; Vasavada et al, 2016; Wang et al, 2013b; Zalsman et al, 2017), other works have found different change directions (similar to our results), as follows. Decreased MD values in MDD were found in left-hemisphere CB (Arnold et al, 2012; Lyden et al, 2014; Wang et al, 2013b) and TF (Lyden et al, 2014; Schnyer et al, 2017; Wang et al, 2013b).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we found generally decreased MD and increased FA in the MDD subjects compared to the healthy controls. While many studies have reported increased MD and decreased FA in MDD compared to HC (Arnold et al, 2012; Benedetti et al, 2011; Osoba et al, 2013; Serafini et al, 2015; Vasavada et al, 2016; Wang et al, 2013b; Zalsman et al, 2017), other works have found different change directions (similar to our results), as follows. Decreased MD values in MDD were found in left-hemisphere CB (Arnold et al, 2012; Lyden et al, 2014; Wang et al, 2013b) and TF (Lyden et al, 2014; Schnyer et al, 2017; Wang et al, 2013b).…”
Section: Discussionsupporting
confidence: 82%
“…While some could not demonstrate a long-term association between WMH progression and depression [ 176 ], large confluent WMHs were associated with a higher incidence of depression in individuals over age 60 years [ 83 ], with persistent depressive symptoms, poorer executive function, and cognitive impairment [ 20 , 177 , 178 ]. WMHs especially within cortico–subcortical neuronal circuits can be interpreted as sequelae of microstructural dysfunctions affecting major brain connections, indicating an association between CVD and depression [ 179 , 180 ], whereas, according to others, structural alterations in the cerebellum may underlie the mechanisms of depressive symptoms in patients with LLD [ 181 ].…”
Section: Structural Brain Lesions In Vadmentioning
confidence: 99%
“…These lesions, associated with CSVD, induce disruptions of frontal–subcortical pathways involved in mood regulation. WMHs are associated with advanced age, cerebrovascular risk factors (diabetes, hypertension, cardiac disease, blood pressure variability, and reduced cerebral blood flow) (for a review, see [38, 121, 197, 198]). The correlation between WMHs and altered default-mode network connectivity supported the role of vascular changes in the etiopathogenesis of VaDep [140, 145] and diminished neuropsychological performance was related to microstructural white matter abnormalities [199].…”
Section: Discussionmentioning
confidence: 99%
“…VaDep is associated with poorer endothelial function, potentially contributing to greater WMH load and basal ganglia microangiopathy [138]. WMHs in patients with LLD, especially within cortico-subcortical neural circuits, should be interpreted as the consequence of underlying microstructural dysfunctions affecting brain connectivity, mediating the association between CSVD and depression [38, 139, 200, 201], although not all studies supported the existence of WMHs as assessed by diffusion tensor imaging MRI in VaDep [202204]. Others, however, suggested that apathy, but not depression, in CSVD is related to damage to cortical–subcortical networks associated with regulation of emotions [155].…”
Section: Discussionmentioning
confidence: 99%